Corrigendum - Bernardo, Luís F. A.; Nepomuceno, Miguel C. S.; Pinto, Hugo A. S. (Journal of Civil Engineering and Management, 2016)
Corrigendum.  Journal of Civil Engineering and Management, 22(8), p. 1088.